Novel 1-(7-ethoxy-1-benzofuran-2-yl) substituted chalcone derivatives: Synthesis, characterization and anticancer activity - Coskun, Demet; Erkisa, Merve; Ulukaya, Engin; Coskun, Mehmet Fatih; Ari, Ferda (Elsevier France-Editions Scientifiques Medicales Elsevier, 2017)
Cancer treatment still requires new compounds to be discovered. Chalcone and its derivatives exhibit anticancer potential in different cancer cells. A new series of benzofuran substituted chalcone derivatives was synthesized by the base-catalyzed Claisen-Schmidt reaction of the 1-(7-ethoxy-1-benzofuran-2-yl) ethanone with different aromatic aldehydes to yield 1-(7-ethoxy-1-benzofuran-2-yl) substituted chalcone derivatives 3a-j. The derivatives were characterized by elemental analysis, FT-IR, H-1 NMR and C-13 NMR spectroscopy techniques. The anti-growth effect of chalcone compounds was tested in breast cancer (MCF-7), non-small cell lung cancer (A549) and prostate cancer (PC-3) cell lines by the SRB and ATP cell viability assays. Apoptosis was detected by mitochondrial membrane potential, Annexin V staining and caspase 3/7 activity. Formation of reactive oxygen species was determined by DCFDA. The results revealed that chalcone derivatives have anticancer activity with especially chalcone derivative 3a showing cytotoxic effects on cancer cells. In addition, chalcone derivative 3a induced apoptosis through caspase dependent pathways in prostate, lung and breast cancer cells. (C) 2017 Elsevier Masson SAS. All rights reserved.
Keywords: Benzofuran; Chalcone; Cytotoxicity; Anticancer activity; Apoptosis